Measuring Health Outcome and Economic Cost associated with Childhood Acute Respiratory Infections: Case of Squatter Settlements in Kathmandu Valley - Pathak, Arjun Bahadur; Adhikari, Naveen (Economic Journal of Development Issues, 2016)
Among the groups of Acute Respiratory Infections (ARIs), pneumonia accounts as the second cause of annual childhood deaths after diarrhea and this is even more serious among poor households and slum areas of Nepal. This study provides an estimate of the household cost associated with ARIs illness and burden of diseases in terms of Disability Adjusted Life Years (DALYs). The data for the analysis have been collected from the households of 15 squatter settlements in Kathmandu Valley. Relevant illness related information with recall period of one month and six months along with socio-economic characteristics of household and family members was collected from the survey. The findings suggest that among the households with affected children within the recall period, 71.66 percent tried some kind of treatment either at home or at health care providers’. The cost composition shows that 92.27 percent indirect costs, 4.77 percent direct cost and 2.96 percent averting cost to households due to childhood ARIs and when "Loss of earning due to premature death" component is not accounted, cost structure is 12.05 percent, 54.27 percent and 33.08 percent respectively. Total discounted years of 70.87 equivalent have been found lost with disability (time lived with sickness or time lost due to death) for under–five children in squatter settlements and yearly 100.05 Quality Adjusted Life Years (QALYs) have been gained due to various treatments-seeking behavior of households in the squatter settlements. Based on the study finding, it is recommended that to minimize total cost of childhood ARIs, households need to offer better averting activities and increase care-seeking behavior to their children.Economic Journal of Development Issues Vol. 17 & 18 No. 1-2 (2014) Combined Issue, Page: 1-18